2018
DOI: 10.1002/j.2334-5837.2018.00569.x
|View full text |Cite
|
Sign up to set email alerts
|

A UAV Case Study with Set‐based Design

Abstract: The DoD and Engineered Resilient Systems (ERS) community seek to leverage the capabilities of model‐based engineering (MBE) early in the design process to improve decision making in AoAs. Traditional tradespace exploration with point‐based design often converges quickly on a solution and engineering changes are required after this selection. Set‐based design considers sets of all possible solutions and enables down‐selecting possibilities to converge at a final solution. Using an Army case study and an open so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…From this set, we identified and collected only refereed journal articles and conference papers, reducing the set to the 64 SBD specific documents considered in the final review. We refer to this set of documents as Group A throughout the remainder of this paper 2–65 . We provide the complete listing for all Group A documents in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…From this set, we identified and collected only refereed journal articles and conference papers, reducing the set to the 64 SBD specific documents considered in the final review. We refer to this set of documents as Group A throughout the remainder of this paper 2–65 . We provide the complete listing for all Group A documents in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Historical analysis of the use of set-based design has shown that it inherently eliminates root causes of rework in system development (Kennedy et al, 2014). Researchers have integrated set-based design with tradespace exploration to further strengthen its value by leveraging the numerous solutions that tradespace exploration provides to generate the initial set (Small et al, 2018). However, empirical research about the implementation of set-based design in an industrial setting showed that there are some discrepancies as to how operationalize the approach (Hansen and Muller, 2012).…”
Section: Set-based Design (Sbd)mentioning
confidence: 99%
“…14 Gundlach’s textbook, “Designing unmanned aircraft systems: a comprehensive approach” 19 is used as the primary basis for all physical architecture descriptions of the notional UAVS and requirements as well as many of the mathematical relationships that propagate design decisions regarding value and cost. 20 Many of the other mathematical relationships are based on observations from UAV descriptions from Compendium Drone 2013. 21…”
Section: Uav Case Studymentioning
confidence: 99%
“…In addition, this research also seeks to develop methods to incorporate MBE, resilience quantification, uncertainty in physics-based parametric performance models, cost, and value models into SBD. This article summaries work from a thesis research project 15 funded by the ERS program.…”
Section: Introductionmentioning
confidence: 99%